STREAMING LAUGHTER: A LINGUISTIC ANALYSIS ON VERBAL HUMOR IN KEVIN HART’S STAND UP COMEDY SPECIAL ZERO F**KS GIVEN - Galant Nanta Adhitya; Devi Rosmawati; Tiara Salma Fainnayla (Universitas Gadjah Mada, 2022)
A novel coronavirus was found on December 2019. WHO named the disease caused by this virus COVID-19. The respiratory virus has been spreading rapidly, causing a global pandemic. To prevent infection, governments all over the world compel their citizens to maintain physical distance and stay at home. Having to do all activities, including working and studying, from home and not being able to gather with family and friends, who do not live in the same household, took a toll on people’s mental health. They thus relied on entertainments accessible at home to avoid boredom and stress. An entertainment medium seeing a significant increase in users is streaming services. Besides offering post-launched movies, TV series and TV show, every streaming service nowadays also produces original contents. Netflix, for example, created a stand-up comedy special starring Kevin Hart, called Zero F**ks Given. The researchers thus aim to analyze the verbal humor Hart uses to incite laughter. The data are collected by watching the show on Netflix website and note-taking its subtitle. Using descriptive qualitative method, this research employs Richard Shade’s theory on humor classification as well as Herbert Paul Grice’s theory on implicature. The findings show there are only 7 out of 12 verbal tumor types, with satire being the most frequent one. Additionally, Hart uses conversational implicature more as it is greatly suitable with satire in inciting laughter.